Analisis Perbandingan Kepuasan Konsumen Terhadap Honda All New PCX-150 dengan Honda ADV-150 di Kota Mataram - Saputra, I Komang Yuda; Zulkarnain, Zulkarnain; Hidayat, Surahman; Wijayanto, Sigit Ary; Wardah, Sofiati (Jurnal Ekonomika Dan Bisnis (JEBS), 2021)
Intense competition in the automotive industry resulted in the emergence of new products that flooded the market from various manufacturers, one of which was the Honda motorcycle dealer company. The AHPCI motorcycle club is an association of consumers who use the Honda All New PCX 150 motorbike while the HAI Lombok Chapter Motor Club is an association of consumers who use the Honda ADV 150. Is there a difference in consumer satisfaction with the Honda ADV 150 and All New PCX 150 motorcycles in Mataram City. Comparative research using 40 samples with an analysis tool of two different tests on average with the results on the product variable no significant difference was found, while on the price variable there was no significant difference while in the accessibility variable there was a significant difference in satisfaction, on the emotional variable there was no difference. significant satisfaction